Development of a conjunctival tissue substitute on the basis of plastic compressed collagen. (10th February 2015) - Drechsler, C. C.; Kunze, A.; Kureshi, A.; Grobe, G.; Reichl, S.; Geerling, G.; Daniels, J. T.; Schrader, S.
Abstract: Ocular surface disorders, such as pterygium, cicatricial pemphigoid and external disruptions, can cause severe inflammation, scarring, fornix shortening as well as ankyloblepharon. Current treatments do not resolve these conditions sufficiently. The aim of this study was to evaluate clinical applicability and suitability of plastic compressed collagen to serve as a substrate for the expansion of human conjunctival epithelial cells in order to develop an epithelialized conjunctival substitute for fornix reconstruction. Human conjunctival epithelial cells were expanded on plastic compressed collagen gels. Epithelial cell characteristics were evaluated by haematoxylin and eosin staining, electron microscopy and cytokeratin expression. The expression of putative epithelial progenitor cell markers p63α, ABCG2 and CK15 was assessed by immunostaining. The proliferative capacity and clonal growth of the cells was evaluated before (P0) and after expansion (P1) on the plastic compressed collagen gels by colony forming efficiency assay. The potential clinical applicability of this gel substitutes was evaluated by assessment of their biomechanical properties as well as their surgical handling. Human conjunctival epithelial cells cultured on plastic and plastic compressed collagen gels formed a confluent cell layer and expressed CK19. The cells showed expression of the putative epithelial progenitor cell markers p63α, ABCG2 and CK15 and sustained colony forming ability. The compressed collagen gels showed a high ultimate tensile strength and elasticity and the surgical handling of gels was comparable to amniotic membrane. An epithelialized conjunctival tissue construct on the basis of compressed collagen might therefore be a promising alternative bioartificial tissue substitute for conjunctival reconstruction. Copyright © 2015 John Wiley & Sons, Ltd.